2016
DOI: 10.1148/radiol.2015150438
|View full text |Cite
|
Sign up to set email alerts
|

Findings from Structural MR Imaging in Military Traumatic Brain Injury

Abstract: Blast-related injury and loss of consciousness is common in military TBI. Structural MR imaging demonstrates a high incidence of white matter T2-weighted hyperintense areas and pituitary abnormalities, with a low incidence of microhemorrhage in the chronic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 39 publications
3
60
1
Order By: Relevance
“…Another consideration in interpreting our findings relates to the effect of white matter hyperintensities, which are common in OEF/OIF veterans with TBI (Riedy et al 2016). There is evidence that these hyperintensities are associated with enhanced white matter abnormalities (Lange et al 2014) as well as with impaired cognition in TBI (Bigler 2006; Clark et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration in interpreting our findings relates to the effect of white matter hyperintensities, which are common in OEF/OIF veterans with TBI (Riedy et al 2016). There is evidence that these hyperintensities are associated with enhanced white matter abnormalities (Lange et al 2014) as well as with impaired cognition in TBI (Bigler 2006; Clark et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in both human and animal models demonstrate TSI as one of the more consistent correlates of cognitive and imaging findings [2, 28, 55, 56]. Namely, with increasing TSI, most TBI (especially mTBI) patients demonstrate improved function [49] and fewer imaging abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The broad category of T2 and FLAIR white matter signal changes was classified as DAI/TAI when there was increased T2 and FLAIR white matter signal in a pattern and distribution that could be consistent with prior traumatic injury. 9,20 Possible DAI/ TAI lesions were typically identified in the subcortical white matter often involving the frontal or parietal lobes; however, we also included periventricular and deep white matter foci in this classification. Other definitions included the following:…”
Section: Mr Imaging Clinical Interpretationmentioning
confidence: 99%
“…A challenge in the interpretation of such structural imaging is determining the importance of imaging findings identified more easily at higher resolution and field strengths. 8 White matter hyperintensities (WMHs), dilated perivascular spaces, pineal gland cysts, and pituitary gland abnormalities have been identified in both mTBI and healthy cohorts, 9,10 and the imaging manifestation of multifocal T2 and FLAIR hyperintensity is visible across conditions including demyelination, inflammation, chronic small vessel ischemia, normal aging, migraine headaches, and moderate/severe TBI. Recent studies in military populations have demonstrated similar rates of WMH in mTBI and non-head trauma groups (Tate et al, 11 41% mTBI versus 49% orthopedically injured versus 29% posttraumatic stress disorder only; and Riedy et al, 9 51.8% mTBI versus 38.1% healthy controls).…”
mentioning
confidence: 99%